2020
DOI: 10.1148/radiol.2019191326
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of American College of Radiology Thyroid Imaging Reporting and Data System (TI-RADS) for Pediatric Thyroid Nodules

Abstract: To assess the performance of the ACR TI-RADS criteria for guiding decisions on whether to biopsy thyroid nodules in pediatric patients in a single referral center. Materials and Methods:In this retrospective study, a database of thyroid nodules in patients younger than 19 years who underwent fine-needle aspiration (FNA) biopsy between January 2004 and July 2017 was analyzed. ACR TI-RADS criteria were applied to each nodule, and an ACR TI-RADS score was created to determine how the nodule would be managed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 17 publications
2
56
0
1
Order By: Relevance
“…A total of 143 FNA samples from 128 patients were identified, with a mean age of 14.9 years (range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 6%) were Bethesda IV, 5 (3.5%) were Bethesda V, and 4 (2.8%) were Bethesda VI. Of the nodules considered Bethesda I by FNA, 13 (48%) were surgically resected and malignancy was identified in 3 (23%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 143 FNA samples from 128 patients were identified, with a mean age of 14.9 years (range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] 6%) were Bethesda IV, 5 (3.5%) were Bethesda V, and 4 (2.8%) were Bethesda VI. Of the nodules considered Bethesda I by FNA, 13 (48%) were surgically resected and malignancy was identified in 3 (23%).…”
Section: Resultsmentioning
confidence: 99%
“…TI-RADS has not yet been adopted for the management of pediatric thyroid nodules. A recent study demonstrated that TI-RADS does not perform optimally in the pediatric population as a significant portion of patients would have a delay in diagnosis of carcinoma [15]. Nevertheless, the use of TI-RADS scores outside of the FNA decision-making algorithm may still be of use in differentiating benign from malignant nodules [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that an experienced thyroid radiologist performs the ultrasound. Reports upon the use of the ACR TIRADS classification as reporting system in children show contradictory re-Eur Thyroid J 2020;9:234-242 DOI: 10.1159/000508872 sults about its adequacy in children [32,33], and no studies exist that evaluate this classification system in children with a germline PTEN mutation. For this reason, no recommendation for using this reporting system can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is the primary imaging test used to detect thyroid nodules, but it has some limitations in showing the relationship of the tumor to the surrounding structures and in identifying lymph node metastasis (4,5). Fine-needle aspiration is an invasive examination, and one-third of the results are inconclusive (3).…”
Section: Introductionmentioning
confidence: 99%